Evaluating the effectiveness of conventional prostheses against dual-mobility prostheses in the treatment of femoral neck fractures in two separate groups of patients: A clinical trial study - Mohammad Parhamfar; Alireza Hosseini; Mostafa Khashei; Mehdi Motififard; Amirmohammad Taravati; Somayeh Shirazinejad; Ali Afsharirad; Amirhossein Sadeghian; Ali Sherafati Chaleshtori (Advanced Biomedical Research, 2023)
Background: Femoral neck fracture is a common posttraumatic injury in the elderly. Currently, orthopedic surgeons conducting total hip arthroplasty (THA) for hip fractures have various prosthetic alternatives. Dual-mobility cup THA is recommended for hip fracture patients to reduce prosthesis dislocation. Therefore, the goal of this research is to evaluate the effectiveness of conventional prostheses against dual-mobility prostheses in treating femoral neck fractures in two groups of patients. Materials and Methods: The current clinical investigation involved patients with femoral neck fractures. Among approved 84 patients, 44 and 40 were undergoing conventional THA (group A) and dual-mobility THA (group B), respectively. Patients were observed regularly after surgeries, and the same measurements were performed. The data were assembled and entered into SPSS software (version 25, IBM Corporation, Armonk, NY, USA) and analyzed. In all analyses, a P value of less than 0.05 was considered significant. Results: Eighty-four cases with an average age of 63.97 years were evaluated. In postoperative follow-up, there were no statistically significant differences between the groups in terms of Harris hip score, SF-36, and infection (P > 0.05). However, patients who received conventional implants had more dislocation postoperatively (P = 0.045). Regarding the rehabilitation costs, there were no statistically significant differences between the groups, so the group using the conventional implants incurred a higher cost (P = 0.041). Conclusion: According to the results, both dual mobility and conventional implants had optimal functional outcomes in patients with femoral neck fractures.